2007
DOI: 10.1007/s00417-007-0612-7
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic membrane as a carrier for lacrimal gland acinar cells

Abstract: Acinar lacrimal gland cells can be successfully cultured on amniotic membrane up to 28 days, with a secretory response to carbachol up to 21 days. This model may be used for further experimental work, to elucidate cellular mechanisms in normal and diseased lacrimal tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…After 3 days of culture on amniotic membrane, we found strong β-hexosaminidase secretion which was about three to four times that of the baseline. The secretory resonse decreased to approximately twice that of the baseline at day 7 and was substantially diminished beyond day 7 2. Similar observations were made by Andersson et al , who reported optimal secretory response of acinar cells after 2–3 days in culture,17 and Schechter et al , who noted a strong reduction in acinar cell secretion beyond day 7 5.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…After 3 days of culture on amniotic membrane, we found strong β-hexosaminidase secretion which was about three to four times that of the baseline. The secretory resonse decreased to approximately twice that of the baseline at day 7 and was substantially diminished beyond day 7 2. Similar observations were made by Andersson et al , who reported optimal secretory response of acinar cells after 2–3 days in culture,17 and Schechter et al , who noted a strong reduction in acinar cell secretion beyond day 7 5.…”
Section: Discussionsupporting
confidence: 84%
“…Several methods have been developed to maintain lacrimal gland cells in vitro,2 3 4 5 6 but preservation of the acinar phenotype and secretory function has proven to be difficult. Rotary cell-culture systems (RCCS) were originally designed to predict the impact of the microgravity environment in space for the culture of cells 7.…”
mentioning
confidence: 99%
“…The simplified procedure did not compromise the purity of LGAC cells and helped to increase the longevity of the primary culture, compatible with recently published protocols (10,11) . Our hypothesis is that reduced manipulation during isolation contributes markedly to improving and extending cell viability and behavior during culture.…”
mentioning
confidence: 66%
“…Several attempts to enhance the growth of acinar cells in culture have been made, but after a span of approximately 3 weeks, LGACs exhibited decreased viability, with high numbers of apoptotic cells (11)(12)(13)(14) . Exocrine acinar cells are fragile, post-mitotic epithelial cells with marked polarity.…”
mentioning
confidence: 99%
“…It also evident that chondrogenic differentiation were enhanced following chemical induction as compared to monolayer cultures, making HAM a potentially suitable material to enhance cellular phenotypic expression. In other studies, the role of HAM, when seeded with stem cells for MSC differentiation, has been documented although all of it were performed in in vivo transplantation without prior in vitro differentiation (Schrader et al 2007;Yang et al 2008). The rationale for phenotypic differentiation was based on the notion that environment induction was adequate to promote the changes without the need for artificial stimulation.…”
Section: Discussionmentioning
confidence: 95%